2022
DOI: 10.1021/acsaenm.2c00119
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide-Enriched Electrospun Nanofibers for Salicylic Acid Controlled Release

Abstract: This work describes a salicylic acid delivery study from electrospun scaffolds that consisted of hydrophilic-like chitosan (CS) and cellulose nanocrystals (CNCs) and hydrophobic-like poly-d,l-lactide (PDLLA) polymers whose final application is wound dressing. The first novel element is represented by the production of hybrid scaffolds made of CNCs, CS, and PDLLA, while the second is their combination with salicylic acid as a drug delivery model. The embedding of poly-d,l-lactide and cellulose nanocrystals in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…An initial burst release is commonly observed for polymer fibers or nanofibers containing drugs, it depends on many factors, for instance, the drug concentration on the fiber surface as well as polymer hydrophobicity and morphology [ 37 , 38 , 39 , 40 , 41 ]. In a recent work, Laezza et al [ 24 ] reported a burst release for electrospun fibers obtained by combining poly- d , l -lactide (PDLLA), cellulose nanocrystals, chitosan and SA. In particular, they found a nearly linear sustained release in their system and a maximum SA release of about 50% [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An initial burst release is commonly observed for polymer fibers or nanofibers containing drugs, it depends on many factors, for instance, the drug concentration on the fiber surface as well as polymer hydrophobicity and morphology [ 37 , 38 , 39 , 40 , 41 ]. In a recent work, Laezza et al [ 24 ] reported a burst release for electrospun fibers obtained by combining poly- d , l -lactide (PDLLA), cellulose nanocrystals, chitosan and SA. In particular, they found a nearly linear sustained release in their system and a maximum SA release of about 50% [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…SA was reported to have antifungal and antibacterial effects, being able to induce morphological and physiological alterations in different compartments of fungal cells and bacteria [ 22 , 23 , 24 ]. Gram-positive and Gram-negative bacteria may colonize medical devices aggregating and growing in a peculiar form of microbial layer of cells attached to a substratum and nested in a matrix of extracellular polymeric materials, defined biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, growing interest has been devoted to fiber scaffolds prepared by electrospinning, allowing the production of distributed fibers with an average diameter ranging from nano-to micrometers, 1,2 to be used for various applications ranging from electrode production and catalysis 3,4 to drug delivery, 5,6 tissue engineering, 7−12 and biosensing, with the latter taking benefit from their biodegradability, nontoxicity, nonmutagenicity, and nonimmunogenicity. 13−15 In this context, the peculiar architecture of e-spun fibers is a critical element, as they perfectly mimic the complexity and threedimensional size of the extracellular matrix (ECM) and act as a physical support for anchoring cells that would regenerate new tissues after injury and damage.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, besides their use for designing sustainable energy storage devices, cellulose-based polymer composites are employed in nanofibrous matrices for applications which range from water filtration 48 to drug release. 49 …”
Section: Introductionmentioning
confidence: 99%
“…46,47 Moreover, besides their use for designing sustainable energy storage devices, cellulose-based polymer composites are employed in nanofibrous matrices for applications which range from water filtration 48 to drug release. 49 Here, we draw a comprehensive outline of a class of environmentally friendly battery separators by employing the amorphous PDLLA as a polymer host with a convenient blend of CNC fillers and investigate how their combination in different ratios can modulate the electrochemical and swelling properties, as well as the nanofibrous morphology.…”
Section: ■ Introductionmentioning
confidence: 99%